Non-valvular infective endocarditis associated with central venous catheter bloodstream infection: a case report - Velarde-Acosta, Kevin (2023)
Non-valvular Infective endocarditis (IE) is exceedingly rare; however, its incidence has risen in tandem with the increased usage of intracardiac devices and the growing prevalence of risk factors associated with IE. We present a clinical case involving an 18-year-old patient with IE occurring at an atypical location, concomitant with central venous catheter bloodstream infection. The patient underwent targeted antibiotic therapy but ultimately required surgical resection of the vegetation due to multiple risk factors associated with a poor prognosis. This case underscores the importance of maintaining a low threshold of suspicion for IE and emphasizes the need for heightened vigilance regarding non-valvular tissues hosting foreign bodies. These less common locations pose a risk for vegetation development. Additionally, we underscore the pivotal role of 3D echocardiography tools in anatomically characterizing the vegetation, including dimensions, implantation area, and related anatomy. These tools provide realistic images that facilitate informed decision-making. Furthermore, the timely selection of surgical intervention in patients at elevated risk of therapeutic failure is a cornerstone in effective management.